2020
DOI: 10.1186/s13045-020-00876-4
|View full text |Cite
|
Sign up to set email alerts
|

How to select IgG subclasses in developing anti-tumor therapeutic antibodies

Abstract: The intact antibody of human immunoglobulin (IgG) is composed of the fragment for antigen binding (Fab) and the crystallizable fragment (Fc) for binding of Fcγ receptors. Among the four subclasses of human IgG (IgG1, IgG2, IgG3, IgG4), which differ in their constant regions, particularly in their hinges and CH2 domains, IgG1 has the highest FcγRbinding affinity, followed by IgG3, IgG2, and IgG4. As a result, different subclasses have different effector functions such as antibody-dependent cell-mediated cytotox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(133 citation statements)
references
References 80 publications
0
104
1
Order By: Relevance
“…The interaction between the Fc domain of an antibody and its cognate FcR triggers a cascade of immune events stimulating phagocytic or cytotoxic cells to eradicate pathogens or infected/tumor cells through different mechanisms, such as antibody-dependent cell-mediated cytotoxicity (ADCC), complement-dependent cytotoxicity (CDC) and antibody-mediated phagocytosis (ADCP) [ 87 , 89 ]. To avoid the killing of T cells that express ICs, most ICIs were developed by choosing antibody isotypes with low or significantly reduced binding to FcRs [ 90 92 ]. Indeed, nivolumab and pembrolizumab, anti-PD-1 antibodies, are IgG4, an isotype considered immunologically inert but that still retains the ability to bind FcγRI and FcγRIIb, activating and inhibitory FcRs, respectively [ 90 92 ].…”
Section: Possible Immune-related Mechanisms Of Hpdmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between the Fc domain of an antibody and its cognate FcR triggers a cascade of immune events stimulating phagocytic or cytotoxic cells to eradicate pathogens or infected/tumor cells through different mechanisms, such as antibody-dependent cell-mediated cytotoxicity (ADCC), complement-dependent cytotoxicity (CDC) and antibody-mediated phagocytosis (ADCP) [ 87 , 89 ]. To avoid the killing of T cells that express ICs, most ICIs were developed by choosing antibody isotypes with low or significantly reduced binding to FcRs [ 90 92 ]. Indeed, nivolumab and pembrolizumab, anti-PD-1 antibodies, are IgG4, an isotype considered immunologically inert but that still retains the ability to bind FcγRI and FcγRIIb, activating and inhibitory FcRs, respectively [ 90 92 ].…”
Section: Possible Immune-related Mechanisms Of Hpdmentioning
confidence: 99%
“…To avoid the killing of T cells that express ICs, most ICIs were developed by choosing antibody isotypes with low or significantly reduced binding to FcRs [ 90 92 ]. Indeed, nivolumab and pembrolizumab, anti-PD-1 antibodies, are IgG4, an isotype considered immunologically inert but that still retains the ability to bind FcγRI and FcγRIIb, activating and inhibitory FcRs, respectively [ 90 92 ]. In this regard, it has been reported that tumor-associated macrophages (TAMs) are able to capture anti-PD-1 antibodies from the T cell membrane through FcγRIIb [ 93 ].…”
Section: Possible Immune-related Mechanisms Of Hpdmentioning
confidence: 99%
“…Fc region containing BsAbs mainly include Duobody( Labrijn et al 2013 ), FIT-Ig (Gong et al 2017 ), 2:2 CrossMab (Brunker et al 2016 ), mAb-Trap (J. Yu et al 2020 ) (Fig. 1 b).…”
Section: Fc Containing Architecturementioning
confidence: 99%
“…This is achieved by combining a low-affinity CD47 arm with a high-affinity CD19 arm, thereby reducing the risk of unwanted CD47 blockade in healthy cells (Buatois et al 2018 ; Hatterer et al 2019 ). Similarly, IMM0306, a CD20 x CD47 BsAb developed by ImmuneOnco has achieved remarkable therapeutic effects in various tumor models and showed no binding to human erythrocytes in pre-clinical study (Yu et al 2020 ). Besides hematological malignancies, there are also BsAbs that work in a similar way to increase blockade/activation specificity in solid tumors, such as IBI322 and RO6874813 (RO7386).…”
Section: Increased Tumor Selectivitymentioning
confidence: 99%
“…More specifically, the IgG2 subclass is commonly selected to neutralize soluble antigens without inducing host effector mechanisms as in the case of erenumab and fremanezumab [ 154 , 155 ]. Similarly, IgG4 such as natalizumab and galcanezumab represent an important subclass of mAbs commonly selected when the recruitment of the host effector mechanisms is not desirable [ 55 , 155 , 159 , 162 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%